Anatomy of the nerves and ganglia of the aortic plexus in males. Issue 1 (9th November 2014) - Beveridge, Tyler S.; Johnson, Marjorie; Power, Adam; Power, Nicholas E.; Allman, Brian L.
Abstract It is well accepted that the aortic plexus is a network of pre‐ and post‐ganglionic nerves overlying the abdominal aorta, which is primarily involved with the sympathetic innervation to the mesenteric, pelvic and urogenital organs. Because a comprehensive anatomical description of the aortic plexus and its connections with adjacent plexuses are lacking, these delicate structures are prone to unintended damage during abdominal surgeries. Through dissection of fresh, frozen human cadavers (n = 7), the present study aimed to provide the first complete mapping of the nerves and ganglia of the aortic plexus in males. Using standard histochemical procedures, ganglia of the aortic plexus were verified through microscopic analysis using haematoxylin & eosin (H&E) and anti‐tyrosine hydroxylase stains. All specimens exhibited four distinct sympathetic ganglia within the aortic plexus: the right and left spermatic ganglia, the inferior mesenteric ganglion and one previously unidentified ganglion, which has been named the prehypogastric ganglion by the authors. The spermatic ganglia were consistently supplied by the L1 lumbar splanchnic nerves and the inferior mesenteric ganglion and the newly characterized prehypogastric ganglion were supplied by the left and right L2 lumbar splanchnic nerves, respectively. Additionally, our examination revealed the aortic plexus does have potential for variation, primarily in the possibility of exhibiting accessory splanchnic nerves. Clinically, our results could have significant implications for preserving fertility in men as well as sympathetic function to the hindgut and pelvis during retroperitoneal surgeries.